Eocene Sediments in the South China Sea, precursor deposits of the Oligocene expansion? - Franz L. Kessler; John Jong; Mazlan Madon (Berita Sedimentologi, 2021)
The stratigraphic record of Eocene in the Malaysian waters of the South China Sea is scarce; the few deep petroleum exploration wells and outcrops are located on the fringes of the SCS. Yet, despite the paucity of data we observe a variety of sediments that cover the range from fluviatile to (at least) neritic marine deposits. Whilst fluvial deposits dominate the Western Rim (Penyu, Malay basins), the Southern Rim (Sarawak) is characterized by deposits of a narrow and rapidly deepening shelf, with fluviatile, shallow marine clastics and carbonates passing seawards to outer shelf and neritic deposits. The proven record of the Eocene to-date is located in relatively small and deep sub-basins.  Possibly, the Eocene underlies additional areas of the SCS, but there is to-date no sufficient well data to offer further confirmation. The presence of Eocene strata on the margins of Sundaland is associated with an early phase of extensional and/or transpressional tectonism, probably acting as precursor movements related to the onset of rifting of the crust underlying the SCS.